DNA targeting by subtype I-D CRISPR–Cas shows type I and type III features. Issue 18 (22nd September 2020) - Lin, Jinzhong; Fuglsang, Anders; Kjeldsen, Anders Lynge; Sun, Kaiyan; Bhoobalan-Chitty, Yuvaraj; Peng, Xu
Abstract: Prokaryotic CRISPR–Cas immune systems are classified into six types based on their effector complexes which cleave dsDNA specifically (types I, II and V), ssRNA exclusively (type VI) or both ssRNA via a ruler mechanism and ssDNA unspecifically (type III). To date, no specific cleavage of ssDNA target has been reported for CRISPR–Cas. Here, we demonstrate dual dsDNA and ssDNA cleavage activities of a subtype I-D system which carries a type III Cas10-like large subunit, Cas10d. In addition to a specific dsDNA cleavage activity dependent on the HD domain of Cas10d, the helicase Cas3′ and a compatible protospacer adjacent motif (PAM), the subtype I-D effector complex can cleave ssDNA that is complementary in sequence to the crRNA. Significantly, the ssDNA cleavage sites occur at 6-nt intervals and the cleavage is catalysed by the backbone subunit Csc2 (Cas7), similar to the periodic cleavage of ssRNA by the backbone subunit of type III effectors. The typical type I cleavage of dsDNA combined with the exceptional 6-nt spaced cleavage of ssDNA and the presence of a type III like large subunit provide strong evidence for the subtype I-D system being an evolutionary intermediate between type I and type III CRISPR–Cas systems.